Zinc(II) Ferrocenylthiosemicarbazone Complexes: Structure, Electrochemistry, Dna Binding And Nuclease Activity - Rajamuthy, Vikneswaran (2011)
Four zinc complexes of the formulae Zn{(η5-C5H5)Fe(η5-C5H4)C(H)=NN=C(S)NH2}2 (V), Zn{(η5-C5H5)Fe(η5-C5H4)C(H)=NN=C(S)N(H) CH3}2∙CH3OH (VI), Zn{(η5-C5H5)Fe(η5-C5H4)C(H)=NN=C(S)N(H)C2H5}2 (VII), Zn{(η5-C5H5)Fe(η5-C5H4)C(H)=NN=C(S)N(H)C6H5}2∙H2O (VIII) have been synthesised and characterised. The structures of these complexes have been established by a single-crystal X-ray diffraction analysis. The coordination geometries of the zinc centres are identical, showing a distorted tetrahedral coordination. The complexes are redox active, giving a reversible cyclic voltammetric response of the Fe(III) − Fe(II) couple near 0.5 V vs. Ag/AgCl. The binding constants, Kb, of the complexes for binding with CT DNA are in the range of 7.0 × 102 to 4.8 × 103 M-1.